2011
DOI: 10.1289/ehp.1003324
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Impaired Glucose Homeostasis Produced in C57BL/6 Mice by Chronic Exposure to Arsenic and High-Fat Diet

Abstract: Background: Type 2 diabetes is characterized by glucose intolerance and insulin resistance. Obesity is the leading cause of type 2 diabetes. Growing evidence suggests that chronic exposure to inorganic arsenic (iAs) also produces symptoms consistent with diabetes. Thus, iAs exposure may further increase the risk of diabetes in obese individuals.Objectives: Our goal was to characterize diabetogenic effects of iAs exposure and high-fat diet (HFD) in weaned C57BL/6 mice.Methods: Mice were fed HFD or low-fat diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
102
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(115 citation statements)
references
References 14 publications
12
102
0
1
Order By: Relevance
“…It is also possible that the observed hyperglycemia is linked to the development of NAFLD, and therefore, additional studies are needed to investigate the effects of fetal arsenic exposure on insulin levels. Nevertheless, the observation that glucose levels increased over time in the IU arsenic-exposed mice is consistent with the epidemiological studies associating type 2 diabetes mellitus with arsenic exposure [29,31], as well as with molecular mechanism and animal studies demonstrating that arsenic may impair insulin response and sensitivity [27,28,43,44].…”
Section: Discussionsupporting
confidence: 87%
“…It is also possible that the observed hyperglycemia is linked to the development of NAFLD, and therefore, additional studies are needed to investigate the effects of fetal arsenic exposure on insulin levels. Nevertheless, the observation that glucose levels increased over time in the IU arsenic-exposed mice is consistent with the epidemiological studies associating type 2 diabetes mellitus with arsenic exposure [29,31], as well as with molecular mechanism and animal studies demonstrating that arsenic may impair insulin response and sensitivity [27,28,43,44].…”
Section: Discussionsupporting
confidence: 87%
“…PTAE treated HFD fed as well as HFD + STZ diabetic mice showed significantly lower blood glucose at all time points and lower AUC when compared to obese control and diabetic control which is shown in Table 4 41,42 . It may be due to the presence of hypoglycemic effect of flavonoids, phenols and saponins present in PTAE which we have reported in our previous study.…”
Section: Discussionmentioning
confidence: 94%
“…Both Type 1 and 2 DM are characterized by hyperglycemia. Interestingly, it has been demonstrated that laboratory animals exposed to inorganic arsenic develop phenotypes consistent with DM, namely increased fasting blood glucose, impaired glucose tolerance and/or insulin resistance (Supplementary Box 1) [19][20][21][22][23][24][25]. Additionally, prenatal exposure to inorganic arsenic predisposes offspring to the development of DM in laboratory studies [26,27].…”
Section: Mechanisms Of Arsenic-associated Dmmentioning
confidence: 99%
“…The fourth mechanism is the induction of gluconeogenesis. While these processes are also involved in Type 2 DM [25], the ability of arsenic to dysregulate these processes supports that it is a diabetogen (Box 1).…”
Section: Mechanisms Of Arsenic-associated Dmmentioning
confidence: 99%
See 1 more Smart Citation